2002
DOI: 10.1038/nbt0102-64
|View full text |Cite
|
Sign up to set email alerts
|

Induction of tumor-specific protective immunity by in situ Langerhans cell vaccine

Abstract: Although anti-tumor immunity is inducible by dendritic cell (DC)-based vaccines, time- and cost-consuming "customizing" processes required for ex vivo DC manipulation have hindered broader clinical applications of this concept. Epidermal Langerhans cells (LCs) migrate to draining lymph nodes and undergo maturational changes on exposure to reactive haptens. We entrapped these migratory LCs by subcutaneous implantation of ethylene-vinyl-acetate (EVA) polymer rods releasing macrophage inflammatory protein (MIP)-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 47 publications
1
64
0
Order By: Relevance
“…The extent of DTH induced by chemoimmunotherapy is also consistent with an increase in the proportion of CD8 + -IFN-γ + cells (39,40). In the present study, increased proportions of IFN-γ-producing CD8 + and CD4 + T cells were observed over time with each treatment; however, the proportions were significantly greater in the patients receiving combination therapy.…”
Section: Discussionsupporting
confidence: 36%
See 1 more Smart Citation
“…The extent of DTH induced by chemoimmunotherapy is also consistent with an increase in the proportion of CD8 + -IFN-γ + cells (39,40). In the present study, increased proportions of IFN-γ-producing CD8 + and CD4 + T cells were observed over time with each treatment; however, the proportions were significantly greater in the patients receiving combination therapy.…”
Section: Discussionsupporting
confidence: 36%
“…Therefore, additional studies with larger numbers of patients and studies taking place at different institutions are necessary to confirm the results of the present study. In addition, the patients in the present study were sensitized to DNP via its topical application; therefore, further studies assessing the possible additive effects of using laser therapy with a previously described DNP-modified melanoma cell vaccine are necessary (33,40). Finally, the mechanism by which combination therapy enhances OS and DFS was not examined.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that ELC/ CCL19 released from polymer rods entrapped migratory Langerhans cells. The Langerhans cells, when loaded with tumor-associated Ags in situ, led to potent CTL activities and protective antitumor immunity (27). Nomura et al (28) showed an enhancement of anti-tumor immunity by tumor cells transfected with ELC/ CCL19 and stromal cell-derived factor-1␣ chemokine genes.…”
Section: Discussionmentioning
confidence: 99%
“…Short term (7-day) Th1 or Th2 cultures were generated from DO11.10 CD4 ϩ T cells in the presence of IL-12 plus anti-IL-4 mAb or IL-4 plus anti-IL-12 mAb, respectively (33). Bone marrowderived DC were generated from BALB/c mice in complete RPMI 1640 medium (34) in the presence of 10 ng/ml GM-CSF as described previously (35,36). The resulting DC preparations harvested on days 5-7 contained 72-92% CD11c ϩ cells and expressed a characteristic phenotype of immature DC.…”
Section: Cd4mentioning
confidence: 99%